Swedish stock and bond returns, 1856 - 2012 - Daniel Waldenström (Uppsala University, Department of Economics, 2014)
This chapter presents historical evidence about Swedish stock prices, dividends, and yields on government fixed-interest securities. Monthly returns are presented since 1901 for stocks, since 1874 for government long-term bonds and since 1856 for short-term Treasury bills or central bank discount rates. Annual stock price and returns indices from 1870 are also presented. Altogether, these series comprise the longest financial asset price database for Sweden to date. An important ambition is to provide information about the quality of the financial data, how they are constructed and how they are modified so as to ensure consistency across time. The chapter also outlines the basic institutional and economic framework of the Swedish stock and money markets. Research has shown that asset prices are influenced by the extent of trading activity as well as by the legal setting and microstructural characteristics. Finally, the chapter offers some initial analysis of the new evidence: calculation of returns for different periods, examination of trends and trend breaks in returns, dividends, volatility and cross-country returns correlations, and computation of equity risk premia across holding periods and historical eras.
urn:nbn:se:uu:diva-225457
Keywords: G12; N23; N24; 330; Historical stock returns; Historical bond yields; Stockholm Stock Exchange; Equity risk premium